Teachers’ and Students’ Perspespectives on the Role of AI in English Language Learning - Handayani, Lista; Rani, Maha; Wahyuni, Sri (Journal of English Language and Education, 2026)
The rapid growth in AI has dramatically changed the way people learn the English language. The present study explores AI integration in the learning process from the perspectives of teachers and students. Qualitative library research was conducted by collecting data from peer-reviewed journals, books, and online scholarly sources on AI applications in education and language learning. Findings indicate that AI offers learners personalized, adaptive, and culturally appropriate learning experiences. Teachers perceive AI to enhance instructional effectiveness and curriculum management, including differentiated instruction; however, professional training, data privacy, and curriculum alignment are mentioned as challenges. Students indicated that AI increases motivation, engagement, and self-regulated learning through interactive exercises and immediate feedback, while usability and guidance are crucial for successful learning. The study concludes that effective AI integration must balance teacher readiness and student engagement along with user-friendly design and continuous evaluation. These insights can help develop effective AI driven English learning strategies.